Dr. Dragoljub Djordjević (1866-1942) Founder and first head of Department Eye District Hospitals in Niš - Stanković-Babić, Gordana; Babić, Rade (Medical Word, 2020)
Ophthalmologist Dr. Dragoljub Djordjević born on 29 December 1866, Belgrade (Serbia), and died on 20 January 1942 Belgrade (Yugoslavia). Author of the ophthalmology in Niš, the founder and first chief of the District Hospital eye department in Niš, the second eye department head of the General State Hospital in Belgrade, a warrior of the Balkan wars and the First World War, the holder of numerous war awards and decorations. He graduated from the Faculty of Medicine in Vienna 1893. The first job is received in Niš decree of August 4th 1894 when he was appointed fizikusa Niš district, district of Pirot. Specilaizaciju from eye diseases Dr Dragoljub Djordjević began 1894 in the eye clinic in Vienna (Austria-Hungary Empire), which quickly left and returned in Niš (Serbia), where environment \ at the hospital in Nis and the Military Hospital in Niš, diagnosed, treated and surgical treated eye disorders. Specialization from eye diseases finished 1903 by professor Dr. Ernst Fuchs with the University Eye Clinic in Vienna. He was appointed the first Chief District Hospital eye department in Niš 1910, which contains the full 16th voluntarily years, with interruptions during the wars. Dr Dragoljub Djordjević 1919 was appointed head of the second eye department of the State General Hospital in Belgrade. His knowledge of ophthalmology unselfish was conveyed to his student Dr. Zdravko Nižetić known by ophthalmologists ceratoplastics.
Keywords: Dr. Dragoljub Djordjević, ophthalmology, eye, First World War, Balkan Front